The Arab uprisings and the politics of contention beyond borders - Fakhoury, Tamirace (2018)
The article draws on the case of the Egyptian uprising between 25 January and 11 February 2011, and maps the transnational practices in which Egyptians in the United States engaged to sustain political ties with Egypt during this period and its direct aftermath. Tracking the involvement of US-based Egyptians through the lens of digital, civic, and epistemic fields, it relates how US-based Egyptians wove a transnational field of contention to boost the uprising’s momentum and renegotiate understandings of political participation. While transnational engagement is credited for refashioning the politics of participation and expanding it beyond territorial sites of governance, it has not had concrete implications for Egypt’s political transition. Transnational non-state activism lost much of its appeal in the US-Egyptian transnational space with the return of the so-called “deep state” after 2013 and the fear of repression. By relating activist strategies to shifting political opportunities, the article provides a broader understanding of the complex interrelationships between emigration and political dynamics within the Arab state.